Food shortages, stockpiling and panic buying ahead of Brexit as reported by the British media: a mixed methods content analysis - Paul C. Coleman; Fatima Dhaif; Oyinlola Oyebode (BMC, 2022)
Abstract Background On 23 June 2016, the United Kingdom voted to leave the European Union. From that date until the UK left the EU in January 2021, there were frequent warnings from industry and government sources of potential disruption to the food supply chain and possible food shortages. Over this period, the media had an important role in communicating on the potential impacts of Brexit. This study examines how food supply and demand, in the context of Brexit, was portrayed by the British media. Methods The study consisted of two components: (1) a quantitative analysis measuring frequency of reporting and information sources for articles on food supply and demand in the context of Brexit, in three daily newspapers, between January 2015 and January 2020; and (2) a content analysis exploring key themes and media framing of relevant issues in a subset of articles. Results Reports by the media about the impact of Brexit on the UK food system were largely absent in the six months before the UK voted to leave the EU in June 2016, increasing in frequency from mid-2018 onward, peaking in mid-2019 following the appointment of Boris Johnson as prime minister. Five themes were developed from included articles: food shortages/panic buying (appearing in 96% of articles); food chain disruption (86%); economic impacts (80%); preparation and stockpiling by the government/food sector (63%) and preparation and stockpiling by individuals (22%). Conclusion Government messaging sought to reassure the public that even under a worst-case scenario there would be no food shortages. These messages, however, contradicted warnings in the media of disruption to the food supply chain and food shortages. The media further reinforced this narrative of potential food shortages by reporting on the experiences of those preparing for Brexit by stockpiling food. The media must consider the impact of their messaging on public behaviour, as even imagined food shortages can instigate stockpiling and panic buying behaviour, as observed during the COVID-19 pandemic.